Legal Regulation of Artificial Intelligence Technology (Case Study of the Russian Federation) - Anton K. KUZNETSOV (Communications of International Proceedings, 2021)
Today the solution of problems of legal regulation of new legal relationships and possible negative effects arising at implementation of digital technologies seems to be important. The article presents an attempt of analysis of legal regulation of artificial intelligence (AI) technologies worldwide, and also international venues on monitoring of AI development. The article observes the experience of Russia on acceleration of technological development, including stimulation of implementation of AI-based technology innovations. The analysis of adopted legal acts and bylaws in the field of legal regulation of AI technologies in the Russian Federation is provided. The tendencies and principles in AI regulation are highlighted. The introduction of experimental legal regimes in the field of digital innovations in Russia (the principle of “regulatory sandboxes”) is considered. Some offers to increase efficiency of digitalization and to minimize new risks are provided.
Keywords: Digital Technologies; Digitalization; Legal Regulation; Artificial Intelligence; E-Person; National Strategy; Information; Information Technology; Robots.